Allocation of maize varieties according to temperature for use in mechanical kernel harvesting in Ningxia, China - Li, Hongyan; Wang, Yonghong; Xue, Jun; Xie, Ruizhi; Wang, Keru; Zhao, Rulang; Liu, Wanmao; Ming, Bo; Hou, Peng; Zhang, Zhentao; et al. (International Journal of Agricultural and Biological Engineering, 2021)
The reasonable assessment of maize varieties in different ecological regions can allow temperature resources to be fully exploited and reach the goal of high yield and efficiency and is thus an important direction of modern maize development in China. In this study, a logistic power nonlinear growth model was used to simulate the accumulated temperature required for kernel dehydration to moisture contents of 25%, 20%, and 16% for various maize cultivar, which were divided into six types based on the accumulated temperature required for kernel dehydration to a moisture content of 25%. The relationship between the yield of maize cultivars and the accumulated temperature required for kernel dehydration to a moisture content of 25% was found to follow a unary function model. Changing the planted maize variety was found to increase economic returns by more than 7000 RMB/hm2 in Ningxia, Northwest China. Under the conditions of mechanical grain harvesting, economic benefits can be further increased by means of selecting high yields and fast-dehydrating varieties, selling when the grain dehydration is below 16%. A better way to achieve grain dehydration to a moisture content below 16% is to postpone the harvest date as much as possible rather than drying after the harvest at physiological maturity. The areas of various types of maize varieties can be dehydrated to moisture contents of 25%, 20%, and 16% were marked. Based on the distribution of heat resources in different regions of Ningxia from the normal sowing date to October 31 before winter irrigation, the appropriate cultivars for various regions in the province were determined based on production benefits. Therefore, in different areas of Ningxia, selecting suitable maize varieties according to temperature resources can reach a high yield and mechanical kernel harvesting, and ultimately obtain higher economic benefits. Keywords: maize, dehydration, grain yield, economic return, mechanical kernel harvesting DOI: 10.25165/j.ijabe.20201401.6035 Citation: Li H Y, Wang Y H, Xue J, Xie R Z, Wang K R, Zhao R L, et al. Allocation of maize varieties according to temperature for use in mechanical kernel harvesting in Ningxia, China. Int J Agric & Biol Eng, 2021; 14(1): 20–28.